Perinatal care for the extremely preterm infant. Issue 2 (April 2022) - Usuda, Haruo; Carter, Sean; Takahashi, Tsukasa; Newnham, John P.; Fee, Erin L.; Jobe, Alan H.; Kemp, Matthew W.
Abstract: Being born preterm (prior to 37 weeks of completed gestation) is a leading cause of childhood death up to five years of age, and is responsible for the demise of around one million preterm infants each year. Rates of prematurity, which range from approximately 5 to 18% of births, are increasing in most countries. Babies born extremely preterm (less than 28 weeks' gestation) and in particular, in the periviable (20 0/7 –25 6/7 weeks) period, are at the highest risk of death, or the development of long-term disabilities. The perinatal care of extremely preterm infants and their mothers raises a number of clinical, technical, and ethical challenges. Focusing on 'micropremmies', or those born in the periviable period, this paper provides an update regarding the aetiology and impacts of periviable preterm birth, advances in the antenatal, intrapartum, and acute post-natal management of these infants, and a review of counselling/support approaches for engaging with the infant's family. It concludes with an overview of emerging technology that may assist in improving outcomes for this at-risk population.